What if… I Asked Cancer Patients About Psychological Distress? Barriers in Psycho-Oncological Screening From the Perspective of Nurses–A Qualitative Analysis - Dreismann, Lara; Goretzki, Alina; Ginger, Viktoria; Zimmermann, Tanja (Frontiers in Psychiatry, 2022)
Introduction Screening questionnaires to assess psychological distress in cancer patients are well-established, but in practice there are difficulties in implementation screening up to referral to psycho-oncology. Interdisciplinary collaboration between psycho-oncology, physicians, and nursing is very important to this process. However, there are barriers and obstacles on all sides. Objective The aim of this study is to capture in particular the barriers from the perspective of oncology nursing. Materials and Methods Semi-structured interviews with nursing experts (n = 15; n = 10 female; 24–62 years) from different oncology departments of three university hospitals in Germanys were conducted and qualitative content analysis was carried out by two raters. Results The Screening routine is variably well-integrated into daily clinical practice. Structural barriers such as time pressure and a lack of focus on mental distress in nursing are present. Barriers on the side of nurses are primarily a lack of knowledge and communication insecurities when dealing with patients. Conclusions There is a need for training and implementation of a disciplinary screening approach. The structural and organizational barriers, which are a challenge for the successful screening process due to unfavorable interdisciplinary team communication and clinical daily structure, should be addressed in further studies. Implications for Practice: In order to establish an interdisciplinary screening process and to overcome the barriers, trainings to deal with knowledge deficits and insecurities seem to be useful.